Filtro híbrido de baixa potência para aplicação em sistemas de baixa tensão - Amorim, Thiago Silva (2016)
This work proposes a low power rating hybrid filter topology and a selective control strategy for the proposed topology. The hybrid filter is composed by a four-branch star passive filter specific configuration and a four leg PWM converter that doesn't have a coupling inductor in the neutral wire. The four-branch star filter is tuned to filter zero-sequence third harmonic and negative-sequence fifth harmonic currents. The proposed selective control strategy uses the phase capacitance and phase and neutral inductances values from the four-branch star filter to determinate current gains. Those gains determine the amount of each harmonic current which the PWM converter must synthesize in order to the hybrid filter mitigates the selected harmonic currents from the source current. The effectiveness of the proposed hybrid topology and the selective control strategy are proved through mathematical analysis and simulations.